Profil Kondisi Fisik Pemain Klub Sepak Bola Brandon Fc Sebelum Dan Pada Saat New Normal - Rahmad Fajri; Pudi M Indika; Ridho Bahtra; Fahmil Haris (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The purpose of this study was to determine the physical condition of Brandon fc players before nd during the new normal. This research is descriptive research. The population in this study were ll football players Brandon fc. The sampling technique used total sampling, the number of samples was 18 people. data nalysis techniques in this study using percentage techniques. The results of the study: (1) The dominant leg muscle power of the Brandon fc player when new normal was 9 people, including the good category. (2) The dominant endurance of Brandon FC players t the time of new normal is 11 people, including the moderate category. (3) The dominant right gility owned by Brandon FC players is 16 people in the good category nd 10 people in the poor category. There is no significant decrease in the explosive power of the leg muscles of the player because the independent training program provided by the coach is carried out seriously by the player.